Antecedents of Individual Taxpayer Compliance: A Social Norm Perspective - Kahfi Fikrianoor; Amir Hidayatulloh (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to analyze the antecedents of taxpayer compliance in terms of social rules. The population of this study is made up of individual taxpayers in Indonesia. The sampling technique uses purposive sampling, with the criteria being that individual taxpayers have a taxpayer identification number. Data collection is done by distributing questionnaires with the help of Google Forms. Data analysis uses Partial Least squares with the help of the WarpPLS tool. This study obtained the results that taxpayer compliance was influenced by personal norms and perceptions of justice, where perceptions of justice were influenced by personal norms. This study also proves that personal norms are a mediating variable, both between descriptive norms, indicative norms, and subjective norms on taxpayer compliance. In addition, this study also found that perceptions of justice mediate the relationship between trust in the government and taxpayer compliance.